2012
DOI: 10.1089/tmj.2011.0272
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Trial of Neuropsychological Evaluations Conducted via Telemedicine in the Veterans Health Administration

Abstract: Neuropsychological evaluation via telemedicine is feasible and appears comparable to in-person evaluation. Experiences are encouraging and consistent with the broader literature on the acceptance of and satisfaction with clinical videoconferencing. Future studies will assess possible psychometric issues in clinical populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 24 publications
0
23
0
2
Order By: Relevance
“…Good agreement was found across most tests examined, with intraclass correlations ranging from .58 to .88. Together with other encouraging findings from the literature using various brief assessments in small groups (Harrell, Wilkins, Connor, & Chodosh, 2014; Jacobsen, Sprenger, Andersson, & Krogstad, 2003; Kirkwood, Peck, & Bennie, 2000; Turner, Horner, VanKirk, Myrick, & Tuerk, 2012; Vestal et al, 2006), these results suggested that VTC-based neuropsychological assessment in older individuals with and without cognitive impairment was feasible and had promising reliability despite that no large-scale studies more definitively establishing reliability had been conducted. Consumer acceptability of VTC-based neuropsychological assessment has also been explored in a recent investigation, with results suggesting good acceptance of VTC-based testing among healthy and cognitively impaired older individuals (Parikh et al, 2013).…”
Section: Introductionmentioning
confidence: 75%
“…Good agreement was found across most tests examined, with intraclass correlations ranging from .58 to .88. Together with other encouraging findings from the literature using various brief assessments in small groups (Harrell, Wilkins, Connor, & Chodosh, 2014; Jacobsen, Sprenger, Andersson, & Krogstad, 2003; Kirkwood, Peck, & Bennie, 2000; Turner, Horner, VanKirk, Myrick, & Tuerk, 2012; Vestal et al, 2006), these results suggested that VTC-based neuropsychological assessment in older individuals with and without cognitive impairment was feasible and had promising reliability despite that no large-scale studies more definitively establishing reliability had been conducted. Consumer acceptability of VTC-based neuropsychological assessment has also been explored in a recent investigation, with results suggesting good acceptance of VTC-based testing among healthy and cognitively impaired older individuals (Parikh et al, 2013).…”
Section: Introductionmentioning
confidence: 75%
“…Two studies compared the accuracy of diagnoses made using the SCID [59,60] , two studies evaluated reliability of child assessments [42,61] , four studies evaluated reliability of neuropsychological assessments [62][63][64][65] , and three studies evaluated reliability of measures of depressive symptom severity [66][67][68] . The remaining studies evaluated a range of targets such as alcohol use severity [69] , diagnostic accuracy [70][71][72] , competency to stand trial [73] , psychosis [26] , and adult autism [21] .…”
Section: Hubley S Et Al Telepsychiatry Reviewmentioning
confidence: 99%
“…While it has been suggested that cognitive screening using telemedicine may be feasible, (23), previous studies have not conducted direct comparisons within subjects. While one recent pilot study compared telemedicine and face-to-face testing (24) and demonstrated that these were comparable, our study looked at interactions over two testing sessions, and included within-subject comparisons. Our study also adds to the growing evidence of applicability of telemedicine-based services for psychiatric care in rural areas (25;26).…”
Section: Discussionmentioning
confidence: 99%